CONSERVATION OF BIOLOGICAL DIVERSITY OF WOODY PLANTS IN EGYPT BY MEANS OF BIOTECHNOLOGICAL METHODS - Kirillov, V.Y.; Serafimovich, M.V. (Eurasian Journal of Applied Biotechnology, 2013)
This article presents a review on conservation of biodiversity of the most valuable woody plants in Egypt by means of methods of biotechnology. Highly effective callus, containing a large number of phenols, was induced from the stems of the seedlings of Delonix elata L. on nutrient medium MS containing 0.5 mg/l of β-naphtyl acetic acid (NAA) and 6-benziladenine (BA) or kinetin. Protocols on reproduction in vitro were worked out for sorts Capparis orientalis Duh. and Capparis leucophylla DC. The method for regeneration of plants from alginate-encapsulated leader shoots was worked out for the sort C. orientalis Duh. With the purpose of working out of a protocol for induction of callus and production of ephedrine from the segments of the stem of Ephedra alata Decne., its induction and extraction were made, as well as ecological conditions in which the given plant grows were investigated. The overcoming of the early ageing of shoots in vitro was studied for Colutea istria Miller which is used for planting of trees and gardens in different landscapes. Clonal reproduction of Acacia saligna (Labill.) H.L.Wendl. was carried out. This economically important sort is used for regeneration of the vegetative cover, agrosilviculture, as forage for animals and as an ornamental plant. Methods of storage in vitro of germoplasma of date-palm Phoenix dactylifera L., which is cultivated for the receiving of sweet fruits, were worked out, as well as methods of its reproduction in vitro by means of direct and indirect proliferation of leader shoots. The method of reproduction in vitro was worked for regeneration of genetic resources of shrubbery Solenostemma arghel (Del). Hayne which had been under the threat of disappearance since natural dispersal by seeds was limited because of excessive grazing of cattle. Leader shoots were used as explants. The method of reproduction in vitro of evergreen shrubbery Simmondsia chinensis (Link) Schn. (jojoba) was worked out, auxiliary branches and nodal segments were used as explants.